Intense zonal freshwater transport in the Eurasian Arctic during ice-covered season revealed by in situ measurements - Alexander Osadchiev; Roman Sedakov; Dmitry Frey; Alexandra Gordey; Vladimir Rogozhin; Zinaida Zabudkina; Eduard Spivak; Ekaterina Kuskova; Andrey Sazhin; Igor Semiletov (Scientific Reports, 2023)
Abstract The Kara Sea receives ~ 1/3 of total freshwater discharge to the Arctic Ocean, mainly from the large Ob and Yenisei rivers. The Ob-Yenisei plume covers wide area in the central part of the Kara Sea during ice-free season (June–October) and accumulates ~ 1000 km3 of freshwater volume. In late autumn, the Kara Sea becomes covered by ice, which hinders in situ measurements at this area. As a result, the fate of the Ob-Yenisei plume below sea ice during winter and spring remains unclear. In this study, we report multiple in situ measurements performed in the Kara Sea shortly before and during ice-covered season. We demonstrate that late autumn convection in the plume shortly before ice formation significantly reduces friction between the plume and the subjacent sea. The subsequent formation of solid sea ice coverage isolates the plume from wind forcing. These two factors precondition the Ob-Yenisei plume to form an intense buoyancy-driven coastal current below sea ice. As a result, the plume advects eastward to the Laptev Sea through the Vilkitsky Strait during several months in November-February. Eventually, by late winter this huge freshwater volume disappears from the Kara Sea and contributes to freshwater content of the Laptev Sea. The obtained result improves our understanding of freshwater balance of the Kara and Laptev seas, as well as provides an important insight into the large-scale freshwater transport in the Eurasian Arctic, which remain largely unknown during ice-covered season.